2012
DOI: 10.1158/1055-9965.epi-12-0202
|View full text |Cite
|
Sign up to set email alerts
|

Pickled Food and Risk of Gastric Cancer—a Systematic Review and Meta-analysis of English and Chinese Literature

Abstract: Background: Ecological and experimental studies have suggested an increased risk of gastric cancer in relation to consumption of pickled vegetables in East Asia.Methods: We conducted a meta-analysis of epidemiologic observational studies to evaluate the existing evidence. Searching PubMed, Vip Chinese Periodical, and China National Knowledge Infrastructure databases, we found a total of 60 studies, 50 case-control, and 10 prospective. We compared gastric cancer risk in pickled vegetable/food users versus nonus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 46 publications
2
58
2
1
Order By: Relevance
“…In fact, most previous studies have reported significant associations between salted vegetable intake and gastric cancer (Lee et al, 1995;Wang et al, 1999;Kim et al, 2010). A meta-analysis showed an increased risk of this cancer with consumption of pickled vegetables in different populations or regions, with OR (95% CI) being 1.89 (1.29-2.77) in Korean, 1.86 (1.61-2.15) in Chinese, and 1.16 (1.04-1.29) in Japanese studies, and 1.14 (0.96-1.35) in studies from other countries (Ren et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, most previous studies have reported significant associations between salted vegetable intake and gastric cancer (Lee et al, 1995;Wang et al, 1999;Kim et al, 2010). A meta-analysis showed an increased risk of this cancer with consumption of pickled vegetables in different populations or regions, with OR (95% CI) being 1.89 (1.29-2.77) in Korean, 1.86 (1.61-2.15) in Chinese, and 1.16 (1.04-1.29) in Japanese studies, and 1.14 (0.96-1.35) in studies from other countries (Ren et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…In the pooled analysis, both 'high' and 'moderately high' salt intake versus 'low' salt intake were significantly associated with increased risk of gastric cancer, with RR of 1.68 (95% CI 1.17-2.41) and 1.41 (1.03-1.93) respectively; the association was found to be stronger in the Japanese population. (48) Additionally, epidemiological and experimental studies (49) have suggested an increased risk of gastric cancer in relation to the consumption of pickled vegetables in East Asia. This issue was addressed in a meta-analysis (49) comparing the gastric cancer risk between people who consumed pickled vegetables/food and non-consumers or those in the lowest reported category of consumption.…”
Section: Diet and Gastric Cancermentioning
confidence: 99%
“…(48) Additionally, epidemiological and experimental studies (49) have suggested an increased risk of gastric cancer in relation to the consumption of pickled vegetables in East Asia. This issue was addressed in a meta-analysis (49) comparing the gastric cancer risk between people who consumed pickled vegetables/food and non-consumers or those in the lowest reported category of consumption. The study reported the following association: (a) overall: OR 1.52, 95% CI 1.…”
Section: Diet and Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…7 Los resultados re cientes de algunos metaanálisis confirman el incremento del riesgo de CG por consumo de sal 13,14 e indican que el consumo de alimentos en escabeche, particularmente de vegetales, también podría incrementarlo. 15,16 Por otra parte, se ha reconocido en la población mexicana que el consumo de sal 8 y de botanas saladas 9 se asocia con un incremento del riesgo de CG (RM= uso de sal, frecuentemente vs nunca =1.83; IC95%: 1.22-2.72, y RM= botanas saladas, >2 veces/mes vs nunca =1.80; IC95%: 1.20-2.80).…”
Section: 9unclassified